MEMBRAN KERAMIK BERPORI BERBAHAN DASAR ZEOLIT DAN CLAY DENGAN PENAMBAHAN ZAT ADITIF - Erlinda Sulistyani; Agus Setyo Budi; Esmar Budi (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2014)
Preparation of porous ceramic membranes have been done. Ceramic membranes based on zeolite, clay, coconut shell activated charcoal, and PVA was made in ten different compositions with clay as a variation of the composition. The addition of additives such as coconut shell activated charcoal and PVA aims to increase the quality of ceramic membranes. In this research, testing water absorption, density, and porosity using standard ASTM C 20-92, as well as testing SEM to see microstructure membrane formed. From the research data obtained to the values of water absorption test are 16.026-75.465%, the values density test are 0.685-1.229 gr/cm3, and the values porosity test are 22.639-59.500%. It can be concluded that the addition of additives decreased density, increased porosity and water absorption of the sample. More perfect pore formation and spread evenly with the addition of the additives. Keywords: membrane, additives, water absorption, density, porosity, SEM.